General View of the Research Studies on World Viticulture In The Last Decade - Zeliha GÖKBAYRAK; Burçak İŞÇİ; Nurhan KESKİN (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
It is seen that research subjects are shaped especially under the effect of climate change and that practices that will minimize possible negative effects are examined. Precision viticulture (modeling with data and image processing) processes for technical and biochemical analysis without damaging the product are gaining momentum. With the effect of changing weather events, variations in diseases and pests are observed and compatible management methods are investigated. The use of non-vine plants under the threat of water scarcity and ensuring that the water can be used by the vine as needed when necessary is a prominent research subject under the threat of global warming. It may be possible to use new markers to develop new drought-resistant varieties. It is noteworthy that relatively few scientific studies have been published on propagation, physiological syndromes, and storage in these journals. In the light of the collected information, projections are expressed with a broad perspective on research topics that can be pursued in the field of viticulture.